An Analysis upon Fluctuation of Gender Inequality in India: Some Challenges: Examining the Challenges and Impacts of Gender Inequality in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Gender-based inequalities in India translate into greater importance being placed on the health and empowerment of males than of females. In India, health and population indicators that are driven by gender differences include sex ratios at birth, infant and child mortality by sex, and low ages at marriage for women. At the household level, dis-empowerment of women results in less access to education, employment, and income, and power and freedom of movement. Considering all these fact, India and its society has a mammoth task of empowering women to provide them the basic needs and to prepare them for a safe and productive future. Despite a high growth rate and plentiful Government measures to encourage gender equality, the gender gap still exists in India. Lack of gender equality not only limits women’s access to resources and opportunities, but also imperils the life prospects of the future generation. In the present article an attempt has been made to examine the problem of gender inequality in India.